1999
DOI: 10.1080/07315724.1999.10718856
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pistachio Nuts on Serum Lipid Levels in Patients with Moderate Hypercholesterolemia

Abstract: Results suggest that eating pistachio nuts instead of other dietary fat calories can improve lipid profiles, thereby decreasing coronary risk. Further studies will be required to confirm these results and to determine the mechanism of this effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
124
1
3

Year Published

1999
1999
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 129 publications
(136 citation statements)
references
References 9 publications
8
124
1
3
Order By: Relevance
“…Incorporation of hazelnut (40 g/day) into human diet favorably altered multiple plasma lipid variables in hypercholesterolemic adult men (Figure 1 and Table 5). Our results are comparable to those reported for other tree nuts such as almond (Hyson et al, 2002), macadamia (Garg et al, 2003), pecan (Rajaram et al, 2001), pistachio (Edwards et al, 1999) and walnut (Zambó n et al, 2000), despite the fact that inclusion of Effects of hazelnut-enriched diet on plasma lipid profiles SM Mercanlıgil et al hazelnut into the human diet in our study was less than half of those reported for other nuts. The intake of SFA generally increases the risk of CHD by increasing the concentrations of total and LDL cholesterol, and Apo B, and increasing the ratios of total/HDL cholesterol and LDL/HDL cholesterol (NRC, 1989).…”
Section: Effects Of Hazelnut-enriched Diet On Plasma Lipid Profiles Ssupporting
confidence: 85%
See 3 more Smart Citations
“…Incorporation of hazelnut (40 g/day) into human diet favorably altered multiple plasma lipid variables in hypercholesterolemic adult men (Figure 1 and Table 5). Our results are comparable to those reported for other tree nuts such as almond (Hyson et al, 2002), macadamia (Garg et al, 2003), pecan (Rajaram et al, 2001), pistachio (Edwards et al, 1999) and walnut (Zambó n et al, 2000), despite the fact that inclusion of Effects of hazelnut-enriched diet on plasma lipid profiles SM Mercanlıgil et al hazelnut into the human diet in our study was less than half of those reported for other nuts. The intake of SFA generally increases the risk of CHD by increasing the concentrations of total and LDL cholesterol, and Apo B, and increasing the ratios of total/HDL cholesterol and LDL/HDL cholesterol (NRC, 1989).…”
Section: Effects Of Hazelnut-enriched Diet On Plasma Lipid Profiles Ssupporting
confidence: 85%
“…Hazelnut-enriched diet compared with baseline favorably altered (Po0.05) these important parameters in cardioprotective direction. Edwards et al (1999) reported that substituting 20% of the daily caloric intake in the form of pistachio nuts after 3-week period significantly reduced both total/HDL cholesterol and LDL/HDL cholesterol ratios in subjects with moderate hypercholesterolemia compared to initial values.…”
Section: Effects Of Hazelnut-enriched Diet On Plasma Lipid Profiles Smentioning
confidence: 98%
See 2 more Smart Citations
“…Studies on properties and bioactivity of this nut to date are limited with respect to other nuts such as walnuts, peanuts, and almonds. Pistachio nut consumption has been shown to have positive effects on serum lipid profile and CVD risk factors in healthy as well as hypercholesterolemic humans [16][17][18][19]. Potential mechanisms of the cardiovascular protective action have been suggested, including effects on plasma stearoyl-CoA desaturase activity [19].…”
Section: Introductionmentioning
confidence: 99%